2004
DOI: 10.3905/jpm.2004.319936
|View full text |Cite
|
Sign up to set email alerts
|

The Equity Premium

Abstract: Recent research on the equity risk premium has questioned the ability of historical estimates of the risk premium to provide reliable estimates of the expected risk premium. We calculate the equity risk premium for a number of countries over longer horizons than has been attempted to date. We show that the realised US equity premium is consistent with the premia obtained elsewhere. Furthermore, using well over a century of data, we find that current estimates of the equity premia are close to those observed du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…• EEP is smaller than HEP according to Copeland et al (2000, HEP-1.5 to 2%); Goedhart et al (2005, HEP-1 to 2%); Bodie, Kane and Marcus (1996, HEP-1%); Mayfield (2004, HEP-2.4%); Booth (1999, 1 Or the extra return that the overall stock market must provide over the Government Bonds to compensate for the extra risk. 2 We agree with Bostock (2004) when he says that "understanding the equity premium is largely a matter of using clear terms". 3 Provided they use the same time frame, the same market index, the same risk-free instrument and the same average (arithmetic or geometric).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…• EEP is smaller than HEP according to Copeland et al (2000, HEP-1.5 to 2%); Goedhart et al (2005, HEP-1 to 2%); Bodie, Kane and Marcus (1996, HEP-1%); Mayfield (2004, HEP-2.4%); Booth (1999, 1 Or the extra return that the overall stock market must provide over the Government Bonds to compensate for the extra risk. 2 We agree with Bostock (2004) when he says that "understanding the equity premium is largely a matter of using clear terms". 3 Provided they use the same time frame, the same market index, the same risk-free instrument and the same average (arithmetic or geometric).…”
Section: Introductionmentioning
confidence: 85%
“…Arnott and Bernstein (2002) also conclude that "the current risk premium is approximately zero". Bostock (2004) concludes that according to historical average data, equities should offer a risk premium over government bonds between 0.6% and 1.8%. Grabowski (2006) concludes that "after considering the evidence, any reasonable long-term estimate of the normal EEP as of 2006 should be in the range of 3.5% to 6%".…”
Section: Other Estimates Of the Expected Equity Premiummentioning
confidence: 99%
“…Instead of trying to find out theoretical vindications for the puzzle some authors resorted to different agendas, like that of providing evidence that the expected, or normal, or theoretical, equity premium is less than the actual premium. See, for example, Arnott and Bernstein (2002), Fama andFrench, (2002), andBostock (2004). However, by surveying the profession, Welch (2000) finds that financial economists estimate the just equity premium to be close to the actual one.…”
Section: Theorymentioning
confidence: 99%
“…They concluded that "the rumours of the predictability of the equity premium are greatly exaggerated". Bostock (2004) developed a framework for constructing an equity risk premium as a combination of required premiums for duration of equities, issuer risk, discretionary income, trading costs, and tax risk. According to his estimates total premium over government bonds should be 1.7%±0.6%.…”
Section: 2 2 D I V I D E N D S a N D E A R N I N G Smentioning
confidence: 99%
“…It is possible, for example, that an environment with both a low level and a low volatility of inflation affects the relative riskiness of stocks and bonds, and hence the risk premium. Bostock (2004) suggests that there is a high correlation over history between the equity risk premium and unanticipated inflation. Campbell and Vuolteenaho (2004) find that the level of inflation explains almost 80% of the time-series variation in stock market mispricing.…”
Section: 3 1 L O W I N F L a T I O N E N V I R O N M E N Tmentioning
confidence: 99%